Legal Analysis of the Sale and Purchase of Dolls from the Viewpoint of Sheikh Yusuf Qardhawi and Sheikh Shalih Utsaimin: A Case Study of the Istana Boneka Shop, Medan Petisah District, Medan City - Lubis, Nurul Hidayah; Suparmin, Sudirman (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
To fulfill their needs, humans engage in buying and selling transactions with one another. One of the items that constitute a tertiary human need is dolls, which are in demand among children and even adults. Scholars agree that dolls are toys that are exempt from the prohibition of statues, but scholars differ on the limits of this exception. This difference of opinion certainly has an impact on the law of buying and selling dolls. Sheikh Al Qardhawi argued that dolls are not haram regardless of their shape, because dolls are not used as a tool of worship and glorification. Sheikh Uthaymeen argued that dolls if their shape is perfect and detailed should be avoided to avoid falling into the act of tashwir. In this study, the researcher used a qualitative method to gain a deeper understanding of the doctrines and views of figures related to the research topic. This research is a field research and uses a normative and sociological approach. The data sources used were interviews and a book entitled Al Halal Wal Haram Fil Islam, and Majm? Fatawa wa Rasail Fadhilah Sheikh Muhammad Bin Salih Al Uthaymeen as primary data. And various literature related to the research topic as secondary data. In analyzing the data, the methods used were descriptive and comparative analysis. At the research location, the Istana Boneka Shop, the dolls sold were both perfectly shaped and imperfect. According to Sheikh Al Qardhawi, buying and selling dolls at the shop is permissible because they are not used as tools of worship or glorification. Meanwhile, according to Sheikh Utsaimin, buying and selling dolls without detailed details is permissible, while dolls with detailed details are makruh (rejected) and very likely to be haram (forbidden). [Dalam memenuhi kebutuhannya manusia melakukan transaksi jual-beli antar satu sama lain. Salah satu barang yang menjadi kebutuhan tersier manusia adalah boneka, yang diminati kalangan anak-anak bahkan orang dewasa. Para ulama sepakat bahwa boneka merupakan mainan yang dikecualikan dari keharaman patung, namun ulama berbeda pendapat mengenai batas pengecualian ini. Perbedaan pendapat ini tentunya berimbas pada hukum jual-beli dari boneka. Syekh Al Qardhawi berpendapat bahwa boneka tidak haram terlepas dari bentuknya, karena boneka tidak digunakan sebagai alat pemujaan dan pengagungan. Syekh Utsaimin berpendapat bahwa boneka apabila bentuknya sempurna dan detail maka harus dijauhi agar tidak terjerumus ke dalam perbuatan tashwir. Dalam penelitian ini peneliti menggunakan metode kualitatif agar bisa memahami lebih dalam doktrin dan pandangan tokoh terkait dengan topik penelitian. Penelitian ini berjenis penelitian lapangan dan menggunakan pendekatan normatif dan sosiologis. Sumber data yang digunakan adalah wawancara dan kitab berjudul Al Halal Wal Haram Fil Islam, dan Majm? Fatawa wa Rasail Fadhilah Syaikh Muhammad Bin Shalih Al Utsaimin sebagai data primer. Dan berbagai literatur yang berkaitan dengan topik penelitian sebagai data sekunder. Dalam menganalisis data, metode yang digunakan adalah analisis deskriptif dan komparatif. Di lokasi penelitian yaitu Toko Istana Boneka, boneka yang dijual berbentuk sempurna dan tidak sempurna. Menurut Syekh Al Qardhawi jual-beli boneka di toko tersebut halal, dikarenakan tidak digunakan sebagai alat penyembahan dan pengagungan. Sedangkan menurut Syekh Utsaimin jual-beli boneka yang tidak detail hukumnya boleh, sedangkan boneka yang detail hukumnya makruh dan sangat mungkin menjadi haram.]